Influence of hyperglycemia on aggregation, deformability and shape parameters of erythrocytes - Babu, N.; Singh, M. (Clinical hemorheology and microcirculation, 2004)
The hemorheological and morphological changes in blood samples of diabetic patients, with varying levels of hyperglycemia but normal cholesterol concentration, are determined and are compared with healthy subjects. The shape analysis is carried out by shape descriptors based on projected area, perimeter and form factor, as measured by processing of images of erythrocytes. The aggregation and deformability of erythrocytes are measured by sequential variation of the transmitted laser light after passing through the erythrocytes suspension in plasma and passage of erythrocytes suspension in physiological saline through cellulose membrane, respectively. The results show that with the increase of glucose concentration the erythrocytes aggregation is enhanced and deformability is reduced in diabetic patients compared to that of healthy subjects. The shape parameters, which quantify the changes in erythrocytes in diabetes, show significant deviation from the shape of normal cells. A significant increase in the perimeter to area ratio and form factor in hyperglycemia also corresponds to highly significant increase in filtration time (decrease in deformability).